2023
DOI: 10.5334/bc.282
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of neighbourhood-scale vertical greening application

Abstract: The warming climate is expected to increase environmental thermal loading on urban buildings. Green infrastructure enhancements have been widely supported as a means to address the resulting heat-related risks, with the challenge of realising enhancements in densely built cities necessitating the consideration of vegetated architectural features. Early efforts promoted horizontal greening, although in recent years 'vertical greening' has gained increased prominence. This paper examines the hypothesis that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…In a detailed five-month experimental campaign conducted in the milder and temperate climate of London (GHI: 1077 kWh/m 2 /y), Doick et al (2014) [96] measured temperature variations in a large greenspace, Kensington Gardens (111 ha) with two ponds (4.9 ha and 2.8 ha), and compared the results with measurements in an adjacent area. They found that the greenery cooled the adjacent space by 1.1 [97] conducted extensive computational fluid dynamics (CFD) modelling and found that a two-hectare green park with a leaf area index (LAI) of 3.16 (forty-five fifty-year-old trees per hectare) could achieve a 4.8 • C air temperature reduction during summertime.…”
mentioning
confidence: 99%
“…In a detailed five-month experimental campaign conducted in the milder and temperate climate of London (GHI: 1077 kWh/m 2 /y), Doick et al (2014) [96] measured temperature variations in a large greenspace, Kensington Gardens (111 ha) with two ponds (4.9 ha and 2.8 ha), and compared the results with measurements in an adjacent area. They found that the greenery cooled the adjacent space by 1.1 [97] conducted extensive computational fluid dynamics (CFD) modelling and found that a two-hectare green park with a leaf area index (LAI) of 3.16 (forty-five fifty-year-old trees per hectare) could achieve a 4.8 • C air temperature reduction during summertime.…”
mentioning
confidence: 99%